2019
DOI: 10.1055/s-0039-1690019
|View full text |Cite
|
Sign up to set email alerts
|

Bicyclic 1-Azafagomine Derivatives: Synthesis and Glycosidase Inhibitory Testing

Abstract: The synthesis of a series of 1-azafagomine derivatives that are tethered with five- and six-membered 1,2-annulated ring systems is described. These compounds were used in order to explore whether a hydrogen-bond acceptor group on the carbon atom corresponding to the glycosidic oxygen is able to interact with the catalytic acidic residue of β-glucosidase. The hydrogen-bond acceptor group was installed at various positions on the annulated ring system making it possible to study the effect of altering the positi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
10
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(11 citation statements)
references
References 28 publications
1
10
0
Order By: Relevance
“…The synthesis of hydrazide imides 4Cl and 5Cl commenced from 2,3,5-tri- O -benzyl- l -xylofuranose ( 7 ) ( Scheme 1 ), which in turn was obtained from l -xylose in three steps by following reported procedures. 24 Thus, by following a protocol reported by Ermert and Vasella for the synthesis of 2,3,4,6-tetra- O -benzyl- d -glucononitrile, 25 condensation of 7 with hydroxyl amine to provide an aldoxime intermediate followed by dehydration under Appel conditions provided nitrile 9 in 52% yield along with known l -xylonolactone 8 . 26 In the subsequent step, compound 9 underwent stereospecific hydrazidation into hydrazide 10 in 54% yield involving triflation of the free hydroxyl group on C4 followed by treatment with Boc-hydrazide.…”
Section: Resultsmentioning
confidence: 99%
“…The synthesis of hydrazide imides 4Cl and 5Cl commenced from 2,3,5-tri- O -benzyl- l -xylofuranose ( 7 ) ( Scheme 1 ), which in turn was obtained from l -xylose in three steps by following reported procedures. 24 Thus, by following a protocol reported by Ermert and Vasella for the synthesis of 2,3,4,6-tetra- O -benzyl- d -glucononitrile, 25 condensation of 7 with hydroxyl amine to provide an aldoxime intermediate followed by dehydration under Appel conditions provided nitrile 9 in 52% yield along with known l -xylonolactone 8 . 26 In the subsequent step, compound 9 underwent stereospecific hydrazidation into hydrazide 10 in 54% yield involving triflation of the free hydroxyl group on C4 followed by treatment with Boc-hydrazide.…”
Section: Resultsmentioning
confidence: 99%
“…Paper / PSP / Special Topic The spectroscopic data were in full accord with the previously reported data. 20 2,3,5-Tri-O-benzyl-D-xylofuranose (D-7) 22 Step 1: To a solution of AcCl (0.29 mL, 4 mmol) in MeOH (40 mL) was added L-xylose (3 g, 20 mmol) at room temp. The reaction was kept stirring at room temp.…”
Section: Synthesismentioning
confidence: 99%
“…As part of our ongoing iminosugar program, 19 20 21 22 we recently reported the synthesis and glycosidase inhibitory activity of compounds d- 2 , d- 3 , and d- 4 (Figure 1 ). 20 The glycosidase inhibitory tests showed that hydrazide imides d- 2 and d- 3 were selective inhibitors (low micromolar range) against jack bean α-mannosidase, which is a member of the retaining glycoside hydrolase family 38 that hosts α-mannosidases of pharmaceutical relevance.…”
Section: Table 1 Screening Of Compounds 2...mentioning
confidence: 99%
See 2 more Smart Citations